Organizational Learning Practices in Public Higher Education Institutions of Ethiopia - Tafesse, Mebratu (Technium Education and Humanities, 2021)
In this study, quantitative research design was employed to examine the relationship between organizational learning practices and institutional performance in Public Higher Education Institutions (HEIs) of Ethiopia. The study investigated: individual, group and organizational level learning practice and their relationship with institutional performance. Data gathered from a 69 item survey questionnaire administrated to 461 academic staff randomly chosen from seven sample public universities from three generations. The finding of the study revealed that individual level learning practice is low, instructors (M=3.67: SD= .562) and academic leaders (M=3.80: SD= .652); group level learning practice is low, instructors (M=3.07, SD=.567) and academic leaders (M = 3.28, SD =.661) and organization level learning is poorly practiced, instructors (M=3.34, SD=.519) and academic leaders (M = 3.58, SD =.670), in public HEIs. In general, it was found that organization learning practice is insufficient, weak and poorly practiced in HEIs as agreed by instructors (M=3.35, SD=.427) and academic leaders (M = 3.56, SD =.581) . It was also concluded that the institutional ability of HEIs to learn from past experiences was insufficient and HEIs were not capable in sharing and utilizing the existing knowledge to create new knowledge to improve institutional practices. Besides, the existing leadership practices, learning infrastructures and technologies could not sufficiently support in transforming HEIs into learning organizations. Therefore, it was suggested that HEIs have to encourage shared and participatory decision-making process; create efficient system and work culture which promote cooperation, trust , team sprit among academic staff and across different disciplines, create long term strategic partnerships with external institutions and facilitate academic mobility and experience sharing activities. Furthermore, learning efforts and outcomes have to be valued and rewarded; technologies and learning infrastructures have be sufficiently developed to support organization wide learning and institutional performance.